Adaptive Behavior as an Alternative Outcome to Intelligence Quotient in Studies of Children at Risk: A Study of Preschool-Aged Children in Flint, MI, USA - Zheng, Shuting; LeWinn, Kaja; Ceja, Tiffany; Hanna-Attisha, Mona; O'Connell, Lauren; Bishop, Somer (Frontiers in Psychology, 2021)
Intelligence quotient (IQ) is commonly measured in child development studies, while adaptive behavior is less frequently considered. Given its associations with functional outcomes in children with neurodevelopmental disabilities, adaptive behavior may be a useful outcome in general population samples, as well. The current study aimed to compare social and environmental correlates of adaptive behavior versus IQ in a sample of preschoolers exposed to the Flint water crisis (N=184). Mother-child dyads were recruited from the community and administered a comprehensive battery to obtain information about child neurodevelopmental functioning, including direct assessment of IQ via the Wechsler Preschool and Primary Scale of Intelligence and assessment of parent-reported adaptive functioning via the Vineland Adaptive Behavior Scales. Multiple social environmental factors were explored as potential correlates of child outcomes (IQ and adaptive behavior), and robust correlates were identified using a data-driven approach (i.e., least absolute shrinkage and selection operator regression; LASSO). We then examined associations between the LASSO selected predictors and IQ and adaptive behavior while controlling for child age, sex, and maternal age. Children in this sample showed relative strength in adaptive behaviors, with scores in the Adequate range, while average IQs fell in the low-average range. Adaptive behavior was significantly associated with maternal nurturance practices, while IQ was associated with maternal education level. Implications for use of adaptive behavior as an outcome measure in studies of children at increased risk for neurodevelopmental problems are discussed.